Prevalence of anxiety and depression among patients with glaucoma - Giacometti, Heloisa Helena Abil Russ; Coelho, Laura Fernandes; Iankilevich, Liana Grupenmacher; Valentin, Livia Stocco Sanches; Ferreira, Luciana Amizo; Balbino, Marcos; Seixas, Regina Cele Silveira (Frontiers in Psychology, 2024)
This study aimed to determine the prevalence of anxiety and depression among patients with glaucoma compared to the average Brazilian prevalence (9.8% of anxiety and 5.8% of depression, according to the World Health Organization) and its correlation with the severity of the disease.Methods: This was a transversal, single-arm trial of patients from four glaucoma centers in Sao Paulo and Curitiba -Brazil. Patients comprised adults at least 18 years of age with glaucoma diagnosis under treatment for at least six months. All subjects of the study answered two questionnaires (PHQ-9 and GAD-7) to evaluate the presence of anxiety and depression, and the results were analyzed accordingly to clinical and demographic characteristics.The protocol included a total of 210 patients. The average age was 61.6 ± 15.3 years, and the female gender was more common (68.86%). Primary open-angle glaucoma was the most common diagnosis (59.90%). The average IOP was 18.5 mmHg, and 1.5 anti-glaucoma drops were the mean treatment.The prevalence of depression and anxiety was 26.90% and 25.71%, respectively.Most patients with anxiety were classified as early glaucoma, while those with depression had severe glaucoma.This study found that the prevalence of anxiety and depression among patients with glaucoma is higher than in the general population in our country.